TINDAK PIDANA PENCUCIAN UANG SEBAGAI FOLLOW UP CRIME DARI TINDAK PIDANA PERJUDIAN (STUDI PUTUSAN NO 40/PID.SUS/2020/PN.JKT.SEL) - Putri Tari Septiani; Ermania Widjajanti (Reformasi Hukum Trisakti, 2023)
Dirty money is a term used to describe money laundering. As is the case in the money laundering case committed by the defendants, specifically defendants I Muslimin, defendant II Kurnia, and defendant III Edi, the money was obtained through gaming and was laundered by receiving a transfer from Barta (DPO). Problem statement: Can the crime of money laundering in this instance be considered a continuation of gambling? and how may the offenders be punished criminally? Analytical descriptive research techniques are used in normative legal research. Due to the fact that they simply take pleasure in or get the proceeds of their crimes, Muslim criminals can be considered passive actors who engage in money laundering. The accused include passive actors who only accept transfers. that is, the crime of money laundering is a follow-up crime of gambling, imposing sanctions on the appropriate defendants, namely Article 5. The conclusion in the court decision in the statute was decided by using Article 10 Jo Article 3 Jo Pasal 2 ayat 1 letter t Law No. 8 year 2010, the defendants should have been dropped by Pasal 5.